Comparisons of three‐dimensional urban forms in different urban expansion types: 58 sample cities in China. (13th October 2020) - Rao, Yingxue; Zhou, Jiang; Zhou, Min; He, Qingsong; Wu, Jiayu
Abstract: Traditional studies of urban spatial expansion typically focus on a single vertical or horizontal dimension and rarely consider the two together. Using 58 cities in China as examples, this paper first identifies the urban growth pattern (UGP) of newly built‐up land patches in each city from 1995 to 2015 horizontally. It then compares and analyses the distribution patterns of three‐dimensional buildings in different UGP patches vertically. There were two important findings: (a) Building patterns in the outlying patches were characterized by low density, high floor numbers, and smooth changes. The infilling patches represented compact development and had the lowest average building height. Edge patches had the highest average number of floors, the most dramatic floor variability, and the lowest utilization rate of three‐dimensional space. (b) In western cities, building distribution characteristics in outlying patches were similar and formed clusters. The distribution characteristics of buildings in the Beijing‐Tianjin‐Hebei urban agglomeration edge patches, as well as those in the northeast urban agglomeration infilling patches, were similar, forming clusters of different types. The results of this paper will contribute to an understanding of both sprawl and the compact development of Chinese cities and will provide international comparative examples.